INTEGRASI PROGRAM ADIWIYATA PADA MAN 1 MALANG DITINJAU DALAM PERSPEKTIF TEORI AGIL OLEH TALCOTT PARSONS - Adistya, Adistya; Humam Farhan Aziz; Putri Anggraini; Afahlul Nur Faizin; Luhung Achmad Perguna (Universitas Negeri Semarang, 2024)
This study aims to examine the results of the implementation of the integration of the MAN 1 Malang adiwiyata program. The Adiwiyata program is a tangible manifestation of the government's commitment to managing and protecting the environment through education. This research uses the perspective of Talcott Parsons' AGIL theory. Data collection techniques used observation, interviews, documentation, and literature study. Then, data analysis techniques include data collection, data reduction, data presentation, and conclusion drawing. The results showed that the implementation of MAN 1 Malang's adiwiyata program has been running, including 1) high ability to adapt to environmental challenges, such as reducing the use of plastics, 2) setting goals both in writing and unwritten, 3) strong coordination between various internal and external actors at MAN 1 Malang, such as the head of madrasah, advisors, chief executives, teachers, students, and external parties, 4) environmental values have been internalized in daily activities at MAN 1 Malang.